Concentration and health risk assessment of toxic metals in giblets of free-range chickens in Lokoja, Nigeria - Jude Ehwevwerhere Emurotu; Tenimu Adogah Abubakar; Loveth Chukwu; Queen Ese Umudi; Victory Imokan Imumorin; Gloria D. Paul; Grace Unekwuojo Oboni (Journal of Trace Elements and Minerals)
Background: Potentially toxic metals present in food and food products are a threat to humans. To monitor the quality of giblets consumed and to evaluate the risk to the public's health, this study aimed to determine the residual concentrations of heavy metals (Al, As, Cd, Cr, Mn, Ni, Pb and Zn) in the gizzard, kidney, and liver of free-range chickens. Methods: The mean concentration of metals in the giblets was determined using Inductively Coupled Plasma Optical Emission Spectrometry. The mean was used to assess the cancer risk, hazard index, total hazard quotient, and estimated daily intake of the metals under investigation. Results: Metal concentrations ranged from 17.6 - 105.6 (Al), nd to 3.15 (As), nd - 4.38 (Cr), 0.26 - 73.6 (Mn), nd - 7.21(Ni), nd - 6.67 (Pb), and 8.42 - 63.3 (Zn) mg kg−1. The mean concentrations measured exceeded JECFA's Maximum Allowable Concentrations limit except for Al and Cd. Cd was below the detection limit. The estimated daily intake of the toxic metals As, Cr, Ni, and Pb exceeded the threshold limit. The metals' calculated Target Hazard Quotient and Hazard Index values were 〈 1. The percentage contribution of Pb to the HI value was the highest. The HI was 66.9% and 65.4% in adults and children, respectively. The HI sequence through the consumption of giblets in adults is Pb 〉 As > Cr > Ni > Zn > Al > Mn. The corresponding sequence in children is Pb > As > Cr > Mn > Ni, Zn > Al. The carcinogenic risk of As, Cr, Ni, and Pb exceeded the threshold limit, indicating a potential cancer risk through consumption. Conclusion: Free-range chickens are not selective in picking their food in the environment hence strict regime of proper disposal of waste products containing metals into the environment should be advocated and followed.